Menanggulangi dampak kekerasan seksual di pondok pesantren: Pendekatan psikoanalisis dalam konteks pendidikan - Anggun Afri Listiana; Anjar Maulana Muhamad; Nasikhin Nasikhin; Fihris Fihris (LP2M Universitas Sarjanawiyata Tamansiswa, 2025)
Sexual violence in Islamic boarding schools, religious-based educational institutions that emphasize moral and spiritual values, is a complex and concerning issue. These cases often lead to stigma that prolongs trauma for the victims. This research uses Sigmund Freud's psychoanalytic theory to analyze the causes and psychological impact of sexual violence, using a case study method. The research involves interviews with victims as well as psychoanalysts or counselors, and data analysis follows the Miles and Huberman method which includes data reduction, data presentation, and conclusion drawing. Sexual violence in Islamic boarding schools can take the form of kissing, hugging, or touching vital parts, often under the guise of affection or orders from authority figures. The psychological impact of victims can be severe, especially since many choose to remain silent. Psychological dynamics that are unconscious and embedded in the victim's subconscious require in-depth exploration. Sexual violence impacts the three psychological components: id, ego, and superego, resulting in repression of traumatic experiences into the subconscious, dissociation, and PTSD symptoms. Healing efforts can be made through exploration of the subconscious with free association, dream analysis, and identification and processing of internal conflicts. This method also involves transference and countertransference. This research is expected to enrich the understanding of the forms of sexual violence in Islamic boarding schools, the psychological mechanisms underlying the impact on victims, and relevant psychological interventions for healing.